Unveiling Language Prejudice: A Corpus-Based Analysis of Racial Slurs Across Genres - Rahman, Fadhlur; Yuzar, Ella; Kholid, Mohammad (Universitas Pendidikan Mandalika, 2024)
Discrimination and racism have been obvious for decades. This encompasses derogatory racial epithets such as